Akuntansi Emak-Emak : Praktik Pengelolaan Dana Arisan Pada Arisan X di Kecamatan Kraksaan - Ela Sari Juniana; Rofiatus Soleha; Linda Kurrotul Aizah; Kamilia Dika Purnamasari; Ekkinanti Zahrani4 (Jurnal Akuntansi Terapan dan Bisnis, 2023)
This study aims to find out how the practice of arisan in Kraksaan District. This research was conducted at the X social gathering community in Kraksaan District. This study uses a descriptive qualitative research method. The data source used is primary data. Primary data is in the form of data taken directly from the object under study through the results of interviews with relevant informants and an understanding of financial management at the arisan, namely the arisan chairman and several arisan members.